(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Guillain Barre Syndrome (GBS) is an acute polyradiculopathy which is quite common in all ages. Objective: The aim of this study was to evaluate the clinical and electrophysiologicaspects of Guillain Barre Syndrome (GBS) in children. Methodology: This cross-sectional study was carried out in the Department of Neurophysiology of National Institute of Neurosciences and Hospital, Bangladesh from July 2016 to June 2018. Patients under 18 years of age fulfilling Brighton diagnostic criteria for GBS were included in this study. These patients were evaluated by detailed history, physical examination, and electrophysiological findings. Results: A total of 82 patients of GBS were enrolled in this study. The mean age was 12.93± 5.02 years (range 1 to<18 years). Most of the patients were male (64.6%) and from the middle-income group (70.73%). About Fourty eight percent of patients had a history of preceding illness among which gastrointestinal infection(24.3%) was the most common. Tingling and paresthesiaswas complained by 32.4% of patients as the first symptom. AMAN(61%) was the most common GBS variant followed by AIDP(26.8%). 9 (11%) patients needed ICU support among them AIDP was more frequent. Conclusion: AMAN is the most common variant among children in this population by electrophysiologic testing. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 2-7